Résolution de problémes de rafle et application á un probléme de frottement - Kaadoud, Mohamed Chraibi (Topological Methods in Nonlinear Analysis, 2001)
In this paper we study the sweeping processes by convexsets depending on time and the solution. We do some application to a dryfriction's problem.